Default ambiguity - Tolulope Fadina; Thorsten Schmidt (Risks, 2019)
This paper discusses ambiguity in the context of single-name credit risk. We focus on uncertainty in the default intensity but also discuss uncertainty in the recovery in a fractional recovery of the market value. This approach is a first step towards integrating uncertainty in credit-risky term structure models and can profit from its simplicity. We derive drift conditions in a Heath-Jarrow-Morton forward rate setting in the case of ambiguous default intensity in combination with zero recovery, and in the case of ambiguous fractional recovery of the market value.
Keywords: 330; model ambiguity; default time; credit risk; no-arbitrage; reduced-form HJM models; recovery process